Organometallic Fe–Fe Interactions: Beyond Common Metal–Metal Bonds and Inverse Mixed‐Valent Charge Transfer. Issue 8 (16th January 2017) - Ringenberg, Mark R.; Schwilk, Max; Wittkamp, Florian; Apfel, Ulf‐Peter; Kaim, Wolfgang
Abstract: The compounds [Fe(CO)3 (dRpf)] n +, n =0, 1, 2 and dRpf=1, 1′‐bis(dicyclohexylphosphino)ferrocene ([1 ] n + ) or 1, 1′‐bis(diisopropylphosphino)ferrocene ([2 ] n + ), were obtained as two‐step reversible redox systems by photolytic and redox reactions. The iron–iron distance decreases from about 4 Å to about 3 Å on oxidation, which takes place primarily at the tricarbonyliron moiety. Whereas ferrocene oxidation is calculated to occur only in excited states, the near infrared absorptions of the mixed‐valent monocations are due to an unprecedented "inverse" inter‐valence charge transfer from the electron‐rich iron(II) in the ferrocene backbone to the electron‐deficient tricarbonyliron(I). Protonation of complex1 results in the formation of the structurally characterized hydride [1 H]BF4, which reacts with acetone to form the dication, 1 2+, and isopropanol. While the hydride [2 H]BF4 was found to be unstable, protonation of2 in acetone resulted in the clean formation of2 2+, formally a hydrogen transfer. Abstract : Two prototypical but very different organoiron moieties, ferrocene and tricarbonyliron, can interact electronically in an intramolecular setting. Unusual oxidation state combinations, structural effects, and redox reactions were observed and analyzed experimentally and theoretically.